Massive Access for Cellular Internet of Things Theory and Technique - Chen, Xiaoming; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on massive access to the cellular internet of things (IoT). Both theory and technique are addressed, with more weight placed on the latter. This is achieved by providing in-depth studies on a number of central topics such as channel state information acquisition, user clustering, superposition coding, and successive interference cancellation. Four typical application scenarios are examined in detail, namely the stationary IoT device scenario, frequency division duplex-based low-mobility IoT device scenario, time-division duplex-based IoT device scenario, and high-mobility IoT device scenario. The comprehensive and systematic treatment of key techniques in massive access to the cellular IoT is one of the major features of the book, which is particularly suited for readers who are interested in finding practical solutions for the cellular IoT. As such, it will benefit researchers, engineers, and graduate students in the fields of information engineering, telecommunications engineering, computer engineering, etc.
Introduction -- Massive Access with Full Channel State Information -- Massive Access with Channel Quantization Codebook -- Massive Access with Channel Reciprocity -- Massive Access with Channel Statistical Information -- Summary.
Keywords: Telecommunication; Wireless communication systems; Mobile communication systems; Electronic circuits; Communications Engineering, Networks; Wireless and Mobile Communication; Electronic Circuits and Systems